The Impact of the New Ordering Strategy on Overârelaxation Variants for Two Dimensional Poissonâs problems - Hasan, M.K. (Springer Science and Business Media Deutschland GmbH, 2022)
The development of a numerical system for the solution of the partial differential equation is very crucial since it can simulate the behavior of many scientific phenomena. The developed system can be used by researchers, educators, and students for research and education purposes. The system was developed using five over-relaxation schemes to solve two-dimensional Poissonâs equations. Besides, the results generated by the system can be exported to Microsoft Excel for further analysis. This system was developed using C # programming languages and ASP.NET. Microsoft SQL Server 2005 is used as a database to store data. In this research, the successive over-relaxation (SOR) method was used as the control of comparison. From the research, the Alternating Top-Down Successive Over Relaxation (AUD-AOR) gives the best performance as compared to others. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.